Hippocampal NMDA receptors and the previous experience effect on memory - Cercato, Magalí Cecilia (2014)
N-methyl-D-aspartate receptors (NMDAR) are thought to be responsible for switching synaptic activity specific patterns into long-term changes in synaptic function and structure, which would support learning and memory. Hippocampal NMDAR blockade impairs memory consolidation in rodents, while NMDAR stimulation improves it. Adult rats that explored twice an open field (OF) before a weak though overthreshold training in inhibitory avoidance (IA), expressed IA long-term memory in spite of the hippocampal administration of MK-801, which currently leads to amnesia. Those processes would involve different NMDARs. The selective blockade of hippocampal GluN2B-containing NMDAR with ifenprodil after training promoted memory in an IA task when the training was weak, suggesting that this receptor negatively modulates consolidation. In vivo, after 1 h of an OF exposure-with habituation to the environment-, there was an increase in GluN1 and GluN2A subunits in the rat hippocampus, without significant changes in GluN2B. Coincidentally, in vitro, in both rat hippocampal slices and neuron cultures there was an increase in GluN2A-NMDARs surface expression at 30 min; an increase in GluN1 and GluN2A levels at about 1 h after LTP induction was also shown. We hypothesize that those changes in NMDAR composition could be involved in the “anti-amnesic effect” of the previous OF. Along certain time interval, an increase in GluN1 and GluN2A would lead to an increase in synaptic NMDARs, facilitating synaptic plasticity and memory; while then, an increase in GluN2A/GluN2B ratio could protect the synapse and the already established plasticity, perhaps saving the specific trace.